The cell : nature's first life-form - Panno, Joseph (New York, NY : Facts on File, 2010)
Covers the recent controversy over the teaching of creationism in public schools, life on other planets, bacterial populations, and the potential threat of certain pathogenic species
1. The origin of life -- 2. Prokaryotes : laying the foundation -- 3. Eukaryotes : dawn of a new era -- 4. The cell cycle -- 5. Genes -- 6. From cells to bodies -- 7. Cells in the human body -- 8. Neurons : pushing back the night -- 9. Plants -- 10. Resource center
Keywords: Cells -- Popular works; Cells -- Evolution -- Popular works